Pengelolaan Aset Nagari oleh Anak Nagari untuk Meningkatkan Pendapatan Asli Nagari (PAN) - Mutia Rahmi; Hasbullah Malau (Journal of Education on Social Science (JESS), 2021)
This study aimed to explain Nagari Asset Management by Nagari people to increase Nagari Income (PAN) in Nagari Minangkabau, Tanah Datar Regency. The research method used is descriptive quasi qualitative. The results showed that the management of nagari assets by nagari people to increase Nagari Original Income (PAN) in Minangkabau Nagari, Tanah Datar Regency consisted of: (a) Planning of village assets has been implemented properly, (b) The utilization of village assets in Nagari Minangkabau, Tanah Datar Regency has not yet carried out optimally, asset utilization has not been implemented in accordance with the specified asset utilization form, (c) Supervision by the Nagari government and custom density village in asset management carried out by the Nagari people is not maximized. Factors that become obstacles in asset management are: (a) The lack of awareness and participation of village people, (b) Incomplete village asset facilities, one of which is incomplete bath, wash and toilet facilities for public bath visitors, (c) Budget issues due to the rehab of public baths that will be carried out, of course, require large funds, (d) Regulatory problems are that there is no village regulation that regulates the management of nagari assets. Based on the obstacles faced, the efforts being made are: (a) Conducting socialization and empowerment to village children, (b) Trying to communicate with all institutional elements and community leaders in the village, (c) Designing Nagari Regulations (PerNag) regarding management village assets.